The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.quascirev.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Extending the record of lacustrine phases beyond the last interglacial for Lake Eyre in central Australia using luminescence dating

Abstract: We show with multiple luminescence dating techniques that the sedimentary record for Lake Eyre, Australia's largest lake, extends beyond 200 thousand years (ka) to Marine Isotope Stage (MIS) 7. Transgressive clayey sand and finely laminated clays overlying the Miocene Etadunna Formation in Lake Eyre North document the deep-lake phases of central South Australia in the past. Until now, unresolved chronology has hampered our ability to interpret these sedimentary records, which are important for understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 139 publications
0
29
0
Order By: Relevance
“…Multigrain residual D e values of 5-19 Gy have been reported for several modern aeolian sediments from Eurasia and South Africa (see Duller and Wintle, 2012). Arnold et al (2014) reported a similarly sized multigrain D e of 7.3 ± 0.8 Gy for a modern slopewash and aeolian deposit from north-central Spain, while multi-grain residual D e values of several tens of Gy have been obtained for coastal and lacustrine shoreline deposits from South Africa and Australia (Jacobs et al, 2011;Fu et al, 2017). In contrast, very large multi-grain TT-OSL residual doses of 250-300 Gy have been reported for modern suspended sediments and overbank deposits from the Yellow River (Hu et al, 2010), potentially cautioning against the suitability of TT-OSL dating in turbid and UVdepleted fluvial settings.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Multigrain residual D e values of 5-19 Gy have been reported for several modern aeolian sediments from Eurasia and South Africa (see Duller and Wintle, 2012). Arnold et al (2014) reported a similarly sized multigrain D e of 7.3 ± 0.8 Gy for a modern slopewash and aeolian deposit from north-central Spain, while multi-grain residual D e values of several tens of Gy have been obtained for coastal and lacustrine shoreline deposits from South Africa and Australia (Jacobs et al, 2011;Fu et al, 2017). In contrast, very large multi-grain TT-OSL residual doses of 250-300 Gy have been reported for modern suspended sediments and overbank deposits from the Yellow River (Hu et al, 2010), potentially cautioning against the suitability of TT-OSL dating in turbid and UVdepleted fluvial settings.…”
Section: Introductionmentioning
confidence: 88%
“…Thirteen samples were collected from actively accumulating, or very recently accumulated, surface sediment deposits that were expected to yield burial doses close to, or consistent with, 0 Gy (assuming adequate signal bleaching during transportation). These samples represent modern analogues for associated archaeological, palaeontological and palaeoenvironmental dating samples being studied as part of recent or ongoing TT-OSL dating projects (e.g., Arnold et al, 2014;Demuro et al, 2014;Fu et al, 2017). Two shallow cave infill samples from the middle Pleistocene palaeoanthropological sites of Galería and Sima del Elefante, Atapuerca, (ATG10-3, ATE10-13) have been chosen for the daylight bleaching experiments, owing to their relatively high and comparable mean burial doses, and uniformly bleached single-grain TT-OSL D e distributions (e.g., Demuro et al, 2014;.…”
Section: Sample Details and Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The abundance of quartz dominated landscapes and the poor preservation of organic remains for other radiometric techniques has resulted in a dominance of the approach in recent literature (e.g. ; Fitzsimmons et al, 2014;Fu et al, 2017;Hughes et al, 2014;Williams et al, 2014Williams et al, , 2017. To date, however, the technique has largely focussed on Indigenous archaeological sites, often of considerable age (Dortch et al, 2016;Veth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%